RECEPTION TO ASSERTIVE SPEECH ACTS IN BARACK OBAMA’S SPEECH ON THE VISIT TO CUBA MARCH 22, 2016: PRAGMATICS STUDIES - Syahrul Rohid; Sutiono Mahdi (IAIN MADURA, 2018)
This article studies about the reception of assertive illocutionary acts in Barack Obama’s speech in Cuba. The purposes of this study are to describe the assertive speech and the reception towards it. The data was taken from Barack Obama’s utterances of assertive speech acts. This study applies qualitative research and descriptive analysis method as a methodology. This study applies Searle and Vanderveken’s assertive speech act classification (1985) and Stuart Hall’s reception theory (1980). Based on this research, the writer found that there are seven kinds of assertive illocutionary acts found in the data: state, remind, suggest, report, inform, assure, and argue. Those illocutionary acts are responded with three reception position found in the data: dominant-hegemonic, oppositional, and negotiated position. The reception position that becomes the most frequent response to Barack Obama’s utterances is an oppositional position. While ‘argue’ are the most frequently used by Barack Obama in his utterances. By arguing his belief, Obama has purpose to assure the hearer. As the United States President, that is in the long conflict with Cuba, his speech must be expressed and delivered clearly in order to influence and to get attention from the hearer.